PEMAHAMAN SISWA KELAS VII SMP DALAM MEMECAHKAN MASALAH SEGIEMPAT BERDASARKAN GAYA KOGNITIF FIELD INDEPENDENT DAN FIELD DEPENDENDENT - Kurniawati, Annisa Dwi; Budayasa, I Ketut; Masriyah, Masriyah (Math Educa Journal, 2024)
Student understanding is one of the interesting topics that is often the subject of research in the scope of mathematics education. On the other hand, cognitive style has a contribution related to student understanding. This study aims to determine how the understanding of junior high school students in solving quadrilateral problems based on cognitive style field independent and field dependent. Qualitative descriptive research involving 2 students consisting of 1 student cognitive style field independent and 1 student cognitive style field dependent. Research data obtained using several instruments namely GEFT, TKM, TPM, and interview guidelines. Furthermore, data checking was carried out using time triangulation. The results showed that the understanding of students in different cognitive styles also showed different understanding when solving problems. At each stage of problem solving, including the stages of understanding the problem, developing a plan, implementing the plan, and checking back, it is described about how the understanding and the extent of the connection of information with the scheme owned by each subject. In full, the understanding of students in solving geometry problems is described comprehensively in the research results section. Students with cognitive style field independent have information linkage with schema that has much more when compared with students with cognitive style field dependent. Based on the results of the study, teachers as educators can pay more attention to students with different cognitive styles when solving math problems. Therefore, instilling understanding and training students in solving mathematical problems is something that teachers should strive for in order to achieve quality learning objectives.